2023
DOI: 10.3390/plants12071456
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Gleditsia sinensis Thorns at Different Stages of Development

Abstract: G. sinensis thorn (called “zào jiǎo cì”, ZJC) has important medicinal and economic value, however, little is known about the molecular mechanisms behind the development of ZJC. In this study, we measured the content of soluble sugar and starch during the growth and development of the thorn, and performed transcriptome sequencing of the thorn segment, non-thorn segment, apex, and root tip at five distinct stages of thorn formation. The results showed that, with the growth of ZJC, the soluble sugar content of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Thus, we predicted that GsinMYB (Gsin11G015360) might regulate the color change from green to yellow brown and then to purple brown by mediating the anthocyanin accumulation. Similarly, earlier investigation proposed that Myb-like, YABBY2, Growth-regulating factor 3, TCP2, Zinc transporter 8 may participate the maintenance and growth of thorns in G. sinensis, helping to elucidate MYB involved in thorns development (Xiao et al, 2023). In castor, the map-based cloning in 2 independent F 2 populations presented the regulatory roles of RcMYB106 about capsule spine development.…”
Section: Gene Co-expression and Potential Tfs Involved In Thorns Deve...mentioning
confidence: 71%
See 2 more Smart Citations
“…Thus, we predicted that GsinMYB (Gsin11G015360) might regulate the color change from green to yellow brown and then to purple brown by mediating the anthocyanin accumulation. Similarly, earlier investigation proposed that Myb-like, YABBY2, Growth-regulating factor 3, TCP2, Zinc transporter 8 may participate the maintenance and growth of thorns in G. sinensis, helping to elucidate MYB involved in thorns development (Xiao et al, 2023). In castor, the map-based cloning in 2 independent F 2 populations presented the regulatory roles of RcMYB106 about capsule spine development.…”
Section: Gene Co-expression and Potential Tfs Involved In Thorns Deve...mentioning
confidence: 71%
“…Light is crucial for the growth, morphology, and developmental changes in plants (de Wit et al, 2016). The photomorphogenesis was reported to participate in thorn development (Xiao et al, 2023). While the detailed role of light in regulating the development of thorns is largely unknown.…”
Section: Potential Key Pathways Involved In Thorns Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…: Leguminosae) is mainly distributed in Asia and America [1]. In China, G. sinensis is the most-used species of Gleditsia in China; it is widely distributed and has various traditional medicinal and culinary applications [2][3][4]. The endosperm of the seeds is edible, while the thorns of G. sinensis can be used as medicine [5], and the pods can be used as a detergent.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [ 10 ] analyzed green, purple, and yellow G. sinensis leaves, and found that differences in the expression of pigment-related genes were related to leaf color. The RNA-seq sequencing and analysis of different developmental tissues and stages of G. sinensis thorns were performed [ 11 ]. The stem tip of different species within the Gleditsia genus were sequencing using the RNA-seq [ 4 ].…”
Section: Introductionmentioning
confidence: 99%